Orchidaceae in the Pieniny Mountains (Western Carpathians) - Frey, Ludwik (Biodiversity: Research and Conservation, 2015)
Orchids constitute an important component of the Pieniny Mts. flora. The presence of 35 orchid species has been noted so far in this region. A considerable number of these species are endangered for various reasons. Eight species have been deemed extinct in the area. On the other hand, the orchid flora of the Pieniny Mts. includes species that widen their local ranges and can, thus, be considered expansive as well as new species, recently entered in the list of orchids occurring in the said mountain range (Epipactis microphylla and Epipactis muelleri). It is necessary and important to conduct an inventory of Pieniny orchid resources (the major aim of this study) that would be repeated at certain intervals, in order to know the number of stations and of individuals per population of each species, which would enable taking relevant actions needed to prevent the disappearance of these plants from the Pieniny Mts.